Multilingual literacies : reading and writing different worlds - Martin-Jones, Marilyn (Studies in written language and literacy ;, 2000)
The research in this unique collection lies at the interface between the fields of bilingualism and literacy. It deepens our understanding of the significance of reading and writing as social practices and opens up new lines of inquiry for research on multilingualism. The authors incorporate theoretical and methodological insights from both fields and provide detailed accounts of everyday practices of reading and writing in different multilingual settings. The focus is primarily on linguistic minority groups in Britain and on the language and literacy experiences of children and adults in rural and urban communities. Together, the chapters of the volume build up a rich and illuminating picture of specific ways in which literacy is bound up with cultural practices and with different ways of seeing the world. They also address fundamental questions about the relationship between language, literacy and power in multi-ethnic contexts.